TEACHING READING SKILLS IN THE MULTICULTURAL WORLD (1st – 4th GRADE): TEACHING READING SKILLS IN THE MULTICULTURAL WORLD (1st – 4th GRADE) - Mandeva, Mariana; Kaneva, Penka (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Problems of teaching reading skills are discussed beyond the context of literary classes - in Bulgarian language classes and in English language classes in Primary school. Motivation for attaining proficiency in reading is considered one of the most important questions in the process of literacy formation. Some interactive techniques of teaching reading in the first (Bulgarian) language are described. Propositions of the second language acquisition theory which English teachers should bear in mind when teach reading in English as a new language are listed.